1997
DOI: 10.1016/s0022-5223(97)70183-1
|View full text |Cite
|
Sign up to set email alerts
|

Fontan operation in five hundred consecutive patients: Factors influencing early and late outcome

Abstract: These analyses indicate that early failure has declined over the study period and that this decline is related in part to procedural modifications. A continuing late hazard phase is associated with few patient-related variables and does not appear related to procedural variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
285
3
10

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 543 publications
(315 citation statements)
references
References 24 publications
(3 reference statements)
17
285
3
10
Order By: Relevance
“…Although the immediate mortality in this series was higher than that reported in the literature 1,[10][11][12][13]16,17 , the late mortality in our group of patients was similar to that found by other authors 15,19 underwent the right atrium-pulmonary artery or Björk techniques, and found a survival rate of 15 years in about 70%, for both techniques. In our group of patients, a high mortality occurred in the immediate postoperative period.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Although the immediate mortality in this series was higher than that reported in the literature 1,[10][11][12][13]16,17 , the late mortality in our group of patients was similar to that found by other authors 15,19 underwent the right atrium-pulmonary artery or Björk techniques, and found a survival rate of 15 years in about 70%, for both techniques. In our group of patients, a high mortality occurred in the immediate postoperative period.…”
Section: Discussionsupporting
confidence: 88%
“…However, if we compare mortality by decades, it decreased by 53% from the 1980s to the 1990s and the year 2000. This decrease was also observed by other authors 10,11,20,21 , proving the technical improvement inherent in to the accumulated experience and to the incorporation of new techniques. In the Boston group 11 , immediate mortality in their initial experience was 27%, rather similar to that in our group.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations